Comment on Falcke et al., "Polymerization, bending, tension: What happens at the leading edge of motile cells?" - Ziebert, Falko; Aranson, Igor S. (European physical journal special topics, 2014)
Commentary on the contribution by M. Falcke and J. Zimmermann [1] in this special issue.